2015
DOI: 10.1016/j.jgar.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

First detection of extended-spectrum cephalosporin- and fluoroquinolone-resistant Escherichia coli in Australian food-producing animals

Abstract: ampicillin (9.4-71.1%), trimethoprim/sulfamethoxazole (11.1-67.5%) and streptomycin (21.9-69.3%), whereas none were resistant to imipenem or amikacin.Resistance was detected, albeit at low frequency, to ESCs (bovine isolates, 1%; porcine isolates, 3%) and FQs (porcine isolates, 1%). Most ESC-and FQ-resistant isolates represented globally disseminated E. coli lineages (ST117, ST744, ST10 and ST1). Only a single porcine E. coli isolate (ST100) was identified as a classic porcine enterotoxigenic E. coli strain (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
97
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(108 citation statements)
references
References 24 publications
11
97
0
Order By: Relevance
“…Transport of pigs between these sites would result in a more widespread spreading of clones [28]. Likewise, in line with previous studies, E. coli may be transmitted from farm to farm by vehicles such as transport trucks and visitors on farms (truck drivers, veterinarians, producers, technicians) or by farm workers [29,30].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Transport of pigs between these sites would result in a more widespread spreading of clones [28]. Likewise, in line with previous studies, E. coli may be transmitted from farm to farm by vehicles such as transport trucks and visitors on farms (truck drivers, veterinarians, producers, technicians) or by farm workers [29,30].…”
Section: Discussionsupporting
confidence: 61%
“…E. coli of phylotypes B2 and D, possessing virulence factors PapC and CNF and serogroup O4, are associated with diseases such as urinary tract infection in humans [40], suggesting a zoonotic potential. Similarly, a recent Australian study reported human-associated zoonotic clones in pigs and cattle [30]. The results observed in the current study are based on our collection that includes 91% pathogenic E. coli from clinical cases.…”
Section: Discussionsupporting
confidence: 55%
“…In contrast, although phylogroup F was rare overall (7%), among non-ST131 isolates it was associated significantly with resistance to fluoroquinolones and/or ESCs. Since both phylogroups B2 and F are associated with extraintestinal virulence (30)(31)(32), their associations here with fluoroquinolone resistance underscore the poten-tial risk of acquiring antimicrobial-resistant pathogenic E. coli from diarrheal feces.…”
Section: Discussionmentioning
confidence: 99%
“…The CoPS isolates were collected during the first national survey of antimicrobial resistance in Australian animal pathogens, which took place over 12 months (January 2013 to January 2014) with the cooperation of all veterinary diagnostic laboratories in each Australian state and territory (n = 22) [23]. Submitting laboratories were instructed to forward coagulase-positive isolates that were considered to be clinically relevant to the presenting condition, as judged by the diagnostic microbiologist.…”
Section: Methodsmentioning
confidence: 99%